China : - Levenson, Joseph R. (University of California Press, 1969)
This is Chinese history to the eng od the first great empire period, in the third century A. D. Many books have been decoted to ancent China, the period in which some of the basic patterns in chinese thought and institutions took shape. First the Chinese world itself is bound together. This is not a mere aggregation of deaths and taxes and bonzes and bronzes. Careers, economics, religion, art, and the other threads of conventional narrative are not left side by side in history, end to end on the page. They interweave convincingly in a satisfying whole. And second, Chinese history is contantly involved in transcendent issues of passive receptacle.